Reduction of androgen induced reactive oxygen species (ROS) production as a method of preventing prostate cancer - Martin, Christopher T. (My University, 2007)
Prostate cancer is a leading cause of cancer deaths among men and development of a preventative agent is urgently needed. Reactive oxygen species (ROS) are carcinogens and are linked to prostate tumor development. ROS production in the prostate is linked to the acetyl polyamine oxidase (APAO) enzyme of the polyamine catabolic pathway. Inhibition of APAO should reduce ROS levels in the prostate and consequently reduce the progression of cancer. CPC-200 is an APAO inhibitor. Previously, our lab conducted studies which indicated that CPC-200 could be effective in reducing ROS levels in the prostate. The purpose of this study was to build on the previous data with additional cell culture and animal studies. Here, we confirm that CPC-200 pretreatment reduces androgen induced oxidative stress. In contrast to previous studies, the current animal studies showed no effect of the CPC-200 treatment. Additional studies are being conducted to further determine the effectiveness of CPC-200.
21 p.
Keywords: Biology; Genetics; Oncology